PREVALENCE OF LOW BIRTH WEIGHT AND ITS ASSOCIATED FACTORS AMONG NEONATES DELIVERED AT DUTSE GENERAL HOSPITAL, JIGAWA STATE (FUDMA JOURNAL OF SCIENCES, 2020)
Birth weight is a significant factor which determines the vulnerability of the child towards developing risks of childhood illness and threat to childhood survival; deviations from normal child birth weight is a significant public health problem globally which is associated with a range of both short- and long-term consequences. The study aimed to assess the prevalence of low birth weight and associated factors among neonates delivered at Dutse General Hospital in Jigawa State. An institutional based retrospective cross sectional study design was used to conduct the study using checklist as the research instrument. A total of 1420 deliveries were recorded during the period of study. Data collected were organized and analysed with SPSS version 20 and results were presented using frequency distribution tables and percentages, mean and standard deviation. The result revealed the prevalence of 13.9% for low birth weight. Maternal age less than 20 years, maternal residence in the rural areas, premature birth, high parity and female infant were associated factors of low birth weight in the Dutse General Hospital. It is recommended that more emphasis should be on antenatal care services to ensure risk of low birth weight is detected early and treated appropriately to improve birth outcomes.
Keywords: Gestational age, Low birth weight, Maternal age, Maternal residence, Prevalence